2017
DOI: 10.1016/j.ihj.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gamma glutamyl transferase as a marker of cardiovascular risk, in 200 angiographically proven coronary artery disease patients

Abstract: Gamma glutamyl transferase (GGT) is emerging as a promising marker for assessing cardiovascular risk. GGT predicts cardiovascular mortality in the population and is positively associated with traditional risk factors for coronary artery disease (CAD). This study was undertaken on 200 north Indian CAD patients diagnosed with coronary angiography to study relation of GGT with risk factors for CAD and severity of CAD. GGT values ranged from 5 to 69U/L and were divided in 4 quartiles. GGT was positively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Further, a number of studies indicated that serum GGT levels were associated with increased risk of myocardial infarction, HF, and mortality after PCI. [2][3][4][5][6][7][16][17][18][19] However, the mechanism of this association remains unclear. Several possible explanations of this association are lack of strong evidences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a number of studies indicated that serum GGT levels were associated with increased risk of myocardial infarction, HF, and mortality after PCI. [2][3][4][5][6][7][16][17][18][19] However, the mechanism of this association remains unclear. Several possible explanations of this association are lack of strong evidences.…”
Section: Discussionmentioning
confidence: 99%
“…H eart failure (HF) is a worldwide epidemic that is associated with considerable hospitalization and mortality. 1 Recently, several studies have shown that elevated g-glutamyl transferase (GGT) levels are associated with increased risk of coronary artery disease (CAD), [2][3][4][5] mortality, 6,7 and HF. 8,9 Wang et al 8 enrolled 18,353 Finnish men and 19,726 women who were 25-74 years of age and free of HF at baseline to investigate the relation between serum GGT levels and HF incidence.…”
Section: Introductionmentioning
confidence: 99%
“…This, together with the dosage of serum levels of troponin and serum levels of some cardiomiochemicaly released isozymes (CK-MB, LDH 1 ) allowed us to rule out the possibility of myocardial ischemia, which would have contributed to the increase in serum concentration of GGT 3 , 7 , 8 .…”
Section: Methodsmentioning
confidence: 99%
“…• family history of CAD 10% [39] Ndrepepa G et al investigated the association between GGT and arterial fibrillation in 5,501 CAD patients. Patients with arterial fibrillation presented elevated serum GGT levels compared to patients with sinus rhythm; 52 U/l versus 34.8 U/l.…”
Section: Ggt and Hypertensionmentioning
confidence: 99%